KOMIK 3D NUSANTARA BERBASIS TECHNOLOGY PEDAGOGICAL CONTENT KNOWLEDGE UNTUK MENINGKATKAN KEMAMPUAN ARITMETIKA SOSIAL SISWA TUNAGRAHITA - Khoirina Muqtafia; Divany Maulida Rizqiyah; Sadana Aura Diva; Josephine Gabriella; Fajar Pamungkas; Jayanti Putri Purwaningrum (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2024)
The aim of this research is to overcome the problem of mental retardation in developing mathematical potential and talent, especially abilities in social arithmetic by providing learning media adapted to the characteristics of mentally retarded students in the form of 3D comics with Indonesian cultural nuances based Technology Pedagogical Content Knowledge (TPACK) assisted by money pyramid media. This is because 11 of the 13 students are still not familiar with the new currency issued by Bank Indonesia, making it difficult for them to spend money. 3D comic media contains stories about traveling to three places in the archipelago which include Bali, Yogyakarta and Bogor, the embossed effect on the paper gives a three-dimensional impression so that it attracts the attention of mentally retarded students to learn using 3D Comics. The money pyramid media is used as the initial foundation for introducing money from one thousand to one hundred thousand denominations to mentally retarded students. The subjects in this research were 13 mentally retarded students in class X C using research methods in the form of experiments. Based on the results of research conducted using data processing, it was found that there were differences in the learning outcomes of mentally retarded students before and after being given treatment in the form of using 3D comic media with nuances of Indonesian culture and money pyramids. The amount of effectiveness in using media influences the learning outcomes of mentally retarded students by 67% in the quite effective category.